Comparison of the prognostic value of platelet-based prognostic models in patients with malignant hepatic tumors after TACE therapy - Du,Qian Cheng (2019)
Abstract Purpose: To investigate the prognostic value of 17 platelet-based prognostic scores in patients with malignant hepatic tumors after TACE therapy. Methods: In total, 92 patients were divided into death group and survival group according to long-term follow-up results. The AUC was calculated to determine the optimal cut-off values for predicting prognosis. To determine better prognostic models, platelet-based models were analyzed separately after being showed as binary according to cut-off values. Cumulative survival rates of malignant hepatic tumors were calculated using Kaplan-Meier curves and differences were analyzed by the log-rank test. Univariate and multivariate analyses were performed to identify platelet-based prognostic scores associated with overall survival. Results: Univariate analysis showed that APGA, APRI, FIB-4, FibroQ, GUCI, King's score, Lok index, PAPAS, cirrhosis, number of tumors, vascular cancer embolus, AFP, ALP and APTT were significantly related to prognosis. A multivariate analysis showed that the APGA, number of tumors, ALP and APTT were independently associated with overall survival. Conclusion: This study showed that the APGA, a platelet-based prognostic score, was an independent marker of prognosis in patients with malignant hepatic tumors after TACE and was superior to the other platelet-based prognostic scores in terms of prognostic ability.